Anti-reflection self-cleaning coating liquid as well as preparation method and application thereof
By using a self-cleaning coating solution that combines polymethyl methacrylate, composite sol and other components, a coating with nano-scale structure is formed, which solves the problem that photovoltaic glass is difficult to achieve both permeability and self-cleaning, and achieves efficient light transmission and self-cleaning effects, and improves the durability and stability of the coating layer.
Patent Information
- Application Number
- CN202510101937.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult for existing photovoltaic glass to achieve good propensity and self-cleaning at the same time, and the durability and stability of the urgency and self-cleaning functional film layer are poor.
A self-cleaning coating liquid with a permeability-enhancing coating solution, whose composition includes polymethyl methacrylate, composite sol, silane, inorganic materials, permeability-enhancing agents and solvents. Through reasonable proportioning and process treatment, a coating with a nano-scale structure is formed to achieve permeability-enhancing and self-cleaning effects.
The light transmittance and self-cleaning properties of photovoltaic glass are significantly improved, and the durability and stability of the coating layer are also optimized.
Smart Images

Figure BDA0005254413040000041 
Figure BDA0005254413040000061 
Figure BDA0005254413040000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of coating liquids, and in particular to an anti-reflective self-cleaning coating liquid and a preparation method and application thereof. Background Art
[0002] With the increasing global emphasis on renewable energy, the photovoltaic industry has experienced rapid growth. As a key component of photovoltaic modules, the performance of photovoltaic glass directly impacts their power generation efficiency. Therefore, research and development of high-performance photovoltaic glass is crucial for improving the overall efficiency of the photovoltaic industry.
[0003] Photovoltaic glass is not only required to have high light transmittance, but also to have self-cleaning properties. To improve the transmittance of solar light and increase the efficiency of photovoltaic power generation systems, some researchers are working on forming anti-reflection coatings on the surface of photovoltaic glass. To improve anti-fouling properties, some are working on forming self-cleaning coatings on the surface of photovoltaic glass. However, existing photovoltaic glass with both self-cleaning properties and good anti-reflection properties struggles to achieve this.
[0004] In addition, when studying the anti-reflection film layer or self-cleaning functional film layer formed on the surface of photovoltaic glass, it was found that this film layer would be affected by factors such as ultraviolet rays, temperature changes, and chemical corrosion and gradually fail, making its durability and stability poor. Summary of the Invention
[0005] In order to solve the above technical problems, the present application provides an anti-reflective self-cleaning coating liquid and a preparation method and application thereof.
[0006] In a first aspect, the present application provides an anti-reflective self-cleaning coating liquid, specifically comprising the following components in parts by weight: 12-18 parts of polymethyl methacrylate, 5-8 parts of composite sol, 3-6 parts of silane, 2-4 parts of inorganic material, 1-3 parts of anti-reflective agent, and 30-40 parts of solvent; The composite sol is obtained by treating a natural polymer colloid and a styrene-acrylonitrile-glycidyl methacrylate copolymer with a 10-20wt% dopamine hydrochloride aqueous solution in a water bath at 80-100°C for 6-10 hours; the weight ratio of the natural polymer colloid, the styrene-acrylonitrile-glycidyl methacrylate copolymer and the dopamine hydrochloride aqueous solution is 20-30:5-10:60-80; The inorganic material is composed of a mixture of 10-30nm silicon dioxide and 40-70nm silicon dioxide in a weight ratio of 0.5-1.5:5-8.
[0007] In the technical solution of this application, in the method for preparing the composite sol, the natural polymer colloid has excellent film-forming properties and transparency, effectively improving the film-forming quality and optical transparency of the coating liquid. Its good adhesion also ensures that the coating liquid firmly adheres to the substrate surface, forming a uniform, transparent film. The styrene-acrylonitrile-glycidyl methacrylate copolymer has excellent weather resistance and chemical corrosion resistance, significantly improving the durability and stability of the coating liquid. This copolymer also forms a good synergistic effect with gum arabic, further enhancing the film-forming properties and transparency of the coating liquid. Dopamine hydrochloride plays a key role in enhancing transmittance and self-cleaning in the coating liquid. Dopamine molecules can self-assemble into nanoscale structures, effectively reducing light reflection on the coating surface and increasing light transmittance, thereby achieving an anti-reflection effect. Furthermore, the applicant has discovered that after the reaction of dopamine hydrochloride with the natural polymer colloid and the styrene-acrylonitrile-glycidyl methacrylate copolymer, it has excellent self-cleaning properties, forming a film on the coating surface that prevents the adhesion of stains and dust, achieving a self-cleaning effect. By rationally proportioning and utilizing gum arabic, styrene acrylonitrile glycidyl methacrylate copolymer and dopamine hydrochloride, a coating liquid with excellent anti-reflection and self-cleaning properties can be prepared.
[0008] In addition, the present application is composed of an inorganic material composed of a mixture of 10-30nm silica and 40-70nm silica in a weight ratio of 0.5-1.5:5-8, which is beneficial for the coating liquid to form a micro-nano structure on the glass surface, thereby improving the transmittance-enhancing self-cleaning coating liquid. Preferably, the anti-reflective self-cleaning coating liquid specifically includes the following components in parts by weight: 14-16 parts of polymethyl methacrylate, 6-7 parts of composite sol, 4-5 parts of silane, 2.5-3.5 parts of inorganic material, 1.5-2.5 parts of anti-reflective agent, and 33-37 parts of solvent.
[0009] Preferably, in the composite sol, the weight ratio of the natural polymer colloid, styrene-acrylonitrile-glycidyl methacrylate copolymer, and dopamine hydrochloride aqueous solution is 22-28:6-9:65-75.
[0010] Preferably, in the composite sol, the natural polymer colloid is selected from one or more of peach gum, gelatin, and gum arabic.
[0011] Preferably, the silane is selected from one or more of aminopropyltriethoxysilane, propyltrimethoxysilane and polydimethylsiloxane.
[0012] Preferably, the permeability enhancer is a mixture of cashew nut shell liquid bio-based polyol and glyceryl tristearate.
[0013] Preferably, the permeability enhancer is composed of a mixture of cashew nut shell liquid bio-based polyol and tristearin in a weight ratio of 7-11:1-3.
[0014] Among transmittance enhancers, the unique chemical structure of cashew nut shell liquid bio-based polyols enables them to effectively improve the optical transparency of the coating liquid. The polyol molecules form good compatibility with other components in the coating liquid, thereby improving the uniformity and transparency of the coating. The bio-based polyols also have good weather resistance and UV resistance, which helps extend the service life of the coating. Tristearin is a highly effective transmittance enhancer that can significantly reduce the surface tension of the coating, making the coating smoother and flatter, thereby reducing light scattering and reflection and increasing light transmittance. Tristearin also has excellent lubricating properties, which can improve the coating's self-cleaning ability and reduce the adhesion of stains and dust.
[0015] Combining cashew nut shell liquid bio-based polyols and glyceryl tristearate can fully utilize the synergistic effect of the two to prepare a coating liquid with excellent anti-reflection and self-cleaning properties. This coating liquid not only has high optical transparency, but also excellent weather resistance and self-cleaning ability.
[0016] Preferably, the solvent is composed of a mixture of n-hexanol and N,N-dimethylacetamide in a weight ratio of 0.5-3:0.5-3.
[0017] Through experimental analysis, it can be seen that the present application selects a mixture of n-hexanol and N,N-dimethylacetamide in the above-mentioned weight ratio to form a solvent, which can further improve the comprehensive performance of photovoltaic glass.
[0018] In a second aspect, the present application provides the application of the above-mentioned antireflection self-cleaning coating liquid in photovoltaic glass materials.
[0019] In a third aspect, the present application provides an antireflective self-cleaning photovoltaic glass, which is prepared using the above-mentioned antireflective self-cleaning coating liquid; specifically, the following steps are performed in sequence: Adding polymethyl methacrylate and composite sol to the solvent in sequence, mixing and stirring evenly; then adding silane, inorganic material and transmittance enhancer, stirring evenly to obtain transmittance-enhancing self-cleaning coating liquid; Take the photovoltaic glass, clean it, blow it dry with nitrogen, and then apply anti-reflection self-cleaning coating liquid on its surface. The coating amount on one side is 30-40g / m 2 ; vacuum drying at 60-80°C for 20-40 minutes, then vacuum drying at 120-140°C for 60-90 minutes, and then curing with ultraviolet light to obtain the product.
[0020] In summary, the technical solution of this application has the following effects: The anti-reflective and self-cleaning coating liquid prepared in this application is used to prepare anti-reflective and self-cleaning photovoltaic glass, which can significantly improve the light transmittance and self-cleaning properties of the photovoltaic glass; and the coating layer has excellent durability and stability.
[0021] The present application further improves the application performance of the anti-reflective self-cleaning coating liquid by optimizing and matching the dosage of each component and simultaneously screening the types of composite sol, inorganic materials, anti-reflective agent and solvent. DETAILED DESCRIPTION
[0022] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in this application.
[0023] Gum arabic (product number: A426754) was purchased from Aladdin; castor oil-modified polyol and cashew nut shell liquid bio-based polyol were purchased from Guangzhou Haoyi New Materials Technology Co., Ltd.; styrene-acrylonitrile-methacrylate copolymer (SAG-002) was purchased from Nantong Rizhisheng Molecular New Materials Technology Co., Ltd. Example
[0024] Examples 1-5 Examples 1-5 respectively provide an anti-reflective self-cleaning coating liquid.
[0025] The difference between the above embodiments is that the amount of each component in the anti-reflection self-cleaning coating liquid is different, as shown in Table 1.
[0026] The preparation method of the antireflection self-cleaning coating liquid in the above embodiment is as follows: (1) Preparation of composite sol: 25 g of natural polymer colloidal gum arabic and 8 g of styrene-acrylonitrile-glycidyl methacrylate copolymer were weighed and placed in 70 g of 15 wt% dopamine hydrochloride aqueous solution, mixed evenly, and heated in a water bath at 90° C. for 8 h to obtain the composite sol.
[0027] (2) According to Table 1, weigh the corresponding weights of the components; Polymethyl methacrylate and composite sol are sequentially added to a solvent (the solvent is composed of a mixture of n-hexanol and N,N-dimethylacetamide in a weight ratio of 2.5:0.8), and mixed at 500 r / min for 10 minutes to obtain uniform mixing; then propyltrimethoxysilane, inorganic material (composed of a mixture of 10-30 nm silica and 40-70 nm silica in a weight ratio of 1:7), and a transmittance enhancer (composed of a mixture of cashew nut shell oil bio-based polyol and tristearate in a weight ratio of 9:2) are added, the speed is adjusted to 1500 r / min, and the mixture is stirred for 30 minutes to obtain a transmittance-enhancing self-cleaning coating liquid.
[0028] Table 1 Amount of each component in the anti-reflection self-cleaning coating liquid in Examples 1-5 and Comparative Examples 1-2 Examples 6-9 Examples 6-9 respectively provide an anti-reflective self-cleaning coating liquid.
[0029] The difference between the above embodiment and embodiment 3 is that the preparation method of the composite sol is different, specifically: in embodiment 6: 20g of natural polymer colloidal gum arabic and 10g of styrene-acrylonitrile-methacrylate glycidyl ester copolymer are weighed and placed in 60g of 10wt% dopamine hydrochloride aqueous solution, mixed evenly, and heated in a water bath at 90°C for 8h to obtain the obtained composite sol.
[0030] In Example 7, 30 g of natural polymer colloidal gum arabic and 5 g of styrene-acrylonitrile-glycidyl methacrylate copolymer were weighed and placed in 80 g of a 20 wt % dopamine hydrochloride aqueous solution, mixed evenly, and heated in a water bath at 90° C. for 8 h to obtain the product.
[0031] In Example 8, 22 g of natural polymer colloidal gum arabic and 9 g of styrene-acrylonitrile-glycidyl methacrylate copolymer were weighed and placed in 65 g of a 12 wt % dopamine hydrochloride aqueous solution, mixed evenly, and heated in a water bath at 90° C. for 8 h to obtain the product.
[0032] In Example 9, 28 g of natural polymer colloidal gum arabic and 6 g of styrene-acrylonitrile-glycidyl methacrylate copolymer were weighed and placed in 75 g of a 17 wt % dopamine hydrochloride aqueous solution, mixed evenly, and heated in a water bath at 90° C. for 8 h to obtain the product.
[0033] The other process parameters in the above embodiment are the same as those in Example 3.
[0034] Examples 10-13 Examples 10-13 respectively provide an anti-reflective self-cleaning coating liquid.
[0035] The difference between the above embodiment and embodiment 3 is that the types of permeability enhancers are different, as shown below.
[0036] In Example 10, the permeability enhancer is composed of a mixture of castor oil-modified polyol and tristearate in a weight ratio of 9:2.
[0037] In Example 11, the permeability enhancer is a mixture of cashew nut shell liquid bio-based polyol and tristearin at a weight ratio of 2:9.
[0038] In Example 12, the permeability enhancer is composed of a mixture of cashew nut shell liquid bio-based polyol and tristearin in a weight ratio of 7:3.
[0039] In Example 13, the permeability enhancer is composed of a mixture of cashew nut shell liquid bio-based polyol and tristearin in a weight ratio of 11:1.
[0040] The other process parameters in the above embodiment are the same as those in Example 3.
[0041] Examples 14-17 Examples 14-17 each provide an anti-reflective self-cleaning coating liquid.
[0042] The difference between the above embodiment and embodiment 3 is that the types of solvents are different, as shown below.
[0043] In Example 14, the solvent is a mixture of n-hexanol and N,N-dimethylacetamide in a weight ratio of 1:1.
[0044] In Example 15, the solvent is a mixture of n-hexanol and N,N-dimethylacetamide in a weight ratio of 0.8:2.5.
[0045] In Example 16, the solvent is a mixture of n-hexanol and N,N-dimethylacetamide in a weight ratio of 2:1.
[0046] In Example 17, the solvent is a mixture of n-hexanol and N,N-dimethylacetamide in a weight ratio of 3:0.5.
[0047] The other process parameters in the above embodiment are the same as those in Example 3.
[0048] Comparative Example Comparative Example 1-2 Comparative Examples 1-2 respectively provide an anti-reflection self-cleaning coating liquid.
[0049] The difference between the comparative example and Example 3 is that the amounts of the components in the anti-reflection self-cleaning coating liquid are different, as shown in Table 1.
[0050] The other process parameters in the above comparative example are the same as those in Example 3.
[0051] Comparative Examples 3-4 Comparative Examples 3-4 each provide an anti-reflective self-cleaning coating liquid.
[0052] The differences between the above comparative example and Example 3 are specifically as follows.
[0053] In Comparative Example 3, the composite sol was prepared by weighing 8 g of natural polymer colloidal gum arabic and 25 g of styrene-acrylonitrile-glycidyl methacrylate copolymer, adding them to 70 g of a 15 wt % dopamine hydrochloride aqueous solution, mixing them evenly, and then heating them in a water bath at 60° C. for 8 h to obtain the result.
[0054] In Comparative Example 4, the inorganic material is composed of a mixture of 10-30 nm silicon dioxide and 40-70 nm silicon dioxide in a weight ratio of 7:1.
[0055] The other process parameters in the above comparative example are the same as those in Example 3.
[0056] Performance testing Take photovoltaic glass, clean it, blow dry it with nitrogen, and then coat the antireflection self-cleaning coating liquid prepared in the embodiment or comparative example on its surface, with a single-side coating amount of 35g / m 2 ; vacuum drying at 70°C for 30 minutes, then vacuum drying at 130°C for 75 minutes, and then curing with ultraviolet light to obtain the product.
[0057] (1) Light transmittance: The transmittance of the coated photovoltaic glass at 600 nm was tested using a UV-3600 spectrophotometer.
[0058] (2) Water contact angle test: The droplet size during the test is 2 μL, and a water contact angle tester is used to test the water contact angle of the coated photovoltaic glass surface.
[0059] (3) Humidity and frost resistance: Tested in accordance with JC / T 2170-2013 / 6.11. Test conditions: relative humidity 85% ± 5%, maximum temperature 85°C ± 2°C decreasing to -40°C ± 2°C, 20 cycles. Measure light transmittance after the test. Humidity and frost resistance = light transmittance after the test / light transmittance before the test × 100%.
[0060] (4) Moisture and heat resistance: Tested in accordance with JC / T 2170-2013 / 6.12, under the following conditions: relative humidity 85% ± 2%, relative humidity 85% ± 2%, for 2000 hours. Measure the light transmittance after the test. Moisture and heat resistance = light transmittance after the test / light transmittance before the test × 100%.
[0061] Test results: as shown in Table 2.
[0062] Table 2 Application performance of the anti-reflective self-cleaning coating liquid in the examples and comparative examples Combined with the test results in Table 2, it can be seen that the anti-reflective and self-cleaning coating liquid prepared using the technical solution of the present application is used to prepare anti-reflective and self-cleaning photovoltaic glass, which can significantly improve the light transmittance of the photovoltaic glass, and its water contact angle is large, indicating high hydrophobicity and high self-cleaning properties; at the same time, the anti-reflective and self-cleaning coating liquid prepared by the present application has excellent durability and stability during actual application.
[0063] By comparing the test results of Examples 1-5 with those of Comparative Examples 1-2, it can be seen that the amount of each component in the anti-reflective self-cleaning coating liquid has a great influence on the performance of the glass. By reasonably controlling the amount ratio of each component, the present application can obtain photovoltaic glass with excellent comprehensive performance.
[0064] By comparing the test results of Examples 3, 6-9 with those of Comparative Example 3, it can be seen that the present application uses natural polymer colloids, styrene-acrylonitrile-methylglycidyl methacrylate copolymers, and dopamine hydrochloride aqueous solution in a weight ratio of 20-30:5-10:60-80 to prepare a composite sol as a raw material component of a transparent and self-cleaning coating liquid, thereby further improving the performance of photovoltaic glass.
[0065] By comparing the test results of Examples 3 and 10-13, it can be seen that the present application uses a mixture of cashew nut shell liquid bio-based polyol and tristearate in a weight ratio of 7-11:1-3 to form a transmittance enhancer, which further improves the performance of photovoltaic glass.
[0066] By comparing the test results of Examples 3 and 14-17, it can be seen that the present application further improves the performance of photovoltaic glass by using a mixture of n-hexanol and N,N-dimethylacetamide in a weight ratio of 0.5-3:0.5-3 to form a solvent.
[0067] Although the present invention has been described in detail above using general descriptions and specific embodiments, it will be apparent to those skilled in the art that modifications and improvements may be made based on the present invention. Therefore, such modifications and improvements, which do not depart from the spirit of the present invention, are intended to be within the scope of protection claimed herein.
Claims
1. A self-cleaning coating liquid with an anti-reflective property, characterized in that: Specifically, it includes the following components in parts by weight: 12-18 parts of polymethyl methacrylate, 5-8 parts of composite sol, 3-6 parts of silane, 2-4 parts of inorganic material, 1-3 parts of permeability enhancer, and 30-40 parts of solvent; The composite sol is obtained by treating a natural polymer colloid and a styrene-acrylonitrile-methacrylate glycidyl copolymer with a 10-20wt% dopamine hydrochloride aqueous solution in a water bath at 80-100°C for 6-10 hours; the weight ratio of the natural polymer colloid, the styrene-acrylonitrile-methacrylate glycidyl copolymer and the dopamine hydrochloride aqueous solution is 20-30:5-10:60-80; The inorganic material is composed of a mixture of 10-30nm silicon dioxide and 40-70nm silicon dioxide in a weight ratio of 0.5-1.5:5-8.
2. The anti-reflection self-cleaning coating liquid according to claim 1, characterized in that: Specifically, the invention comprises the following components in parts by weight: 14-16 parts of polymethyl methacrylate, 6-7 parts of composite sol, 4-5 parts of silane, 2.5-3.5 parts of inorganic material, 1.5-2.5 parts of permeability enhancer and 33-37 parts of solvent.
3. The anti-reflection self-cleaning coating liquid according to claim 1, characterized in that: In the composite sol, the weight ratio of natural polymer colloid, styrene-acrylonitrile-glycidyl methacrylate copolymer and dopamine hydrochloride aqueous solution is 22-28:6-9:65-75.
4. The anti-reflection self-cleaning coating liquid according to claim 1, characterized in that: In the composite sol, the natural polymer colloid is selected from one or more of peach gum, gelatin and gum arabic.
5. The anti-reflection self-cleaning coating liquid according to claim 1, characterized in that: The silane is selected from one or more of aminopropyltriethoxysilane, propyltrimethoxysilane and polydimethylsiloxane.
6. The anti-reflection self-cleaning coating liquid according to claim 1, characterized in that: The permeability enhancer is a mixture of cashew nut shell oil bio-based polyol and tristearic acid glyceryl.
7. The anti-reflection self-cleaning coating liquid according to claim 1, characterized in that: The permeability enhancer is composed of a mixture of cashew nut shell oil bio-based polyol and tristearic acid glyceryl in a weight ratio of 7-11:1-3.
8. The anti-reflection self-cleaning coating liquid according to claim 1, characterized in that: The solvent is composed of a mixture of n-hexanol and N,N-dimethylacetamide in a weight ratio of 0.5-3:0.5-3.
9. Use of the anti-reflection self-cleaning coating liquid according to any one of claims 1 to 8 in photovoltaic glass materials.
10. An anti-reflective self-cleaning photovoltaic glass, characterized in that: The method is prepared by using the anti-reflection self-cleaning coating liquid according to any one of claims 1 to 8; specifically comprising the following steps in sequence: Adding polymethyl methacrylate and composite sol to the solvent in sequence, mixing and stirring evenly; then adding silane, inorganic material and permeability enhancer, stirring evenly, to obtain a permeability enhancer self-cleaning coating liquid; Take the photovoltaic glass, clean it, blow it dry with nitrogen, and then apply the anti-reflection self-cleaning coating liquid on its surface. The coating amount on one side is 30-40g / m 2 ; vacuum drying at 60-80°C for 20-40min, then vacuum drying at 120-140°C for 60-90min, and then curing with ultraviolet light to obtain the product.
Citation Information
Patent Citations
Cashew nut phenol-amine polyalcohol and preparation method thereof
CN102875394A
Boron nitride doped cardanol-based polyurethane capable of being repeatedly processed as well as preparation method and application of cardanol-based polyurethane
CN118359783A
Single-component solvent-free weather-resistant polyurethane elastomer composition and preparation method thereof
CN118546601A
Cited By
Antioxidant neodymium iron boron magnet and preparation method thereof
CN120511132A
An oxidation-resistant neodymium-iron-boron magnet and a method for manufacturing the same
CN120511132B